PEDAGOGICAL CONDITIONS FOR PREPARING STUDENTS OF A PEDAGOGICAL UNIVERSITY TO TEACH RUSSIAN - Zokir Avliyakulov; Lyudmila I. Ponomareva (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. The article notes that the socio-economic changes taking place in society place on higher education in the Republic of Uzbekistan the task of solving problems related to the development, in graduates of pedagogical universities, of professional competences that ensure the successful organization of the educational process at school. At the social, scientific-theoretical and technological levels, the formation of a future teacher who is consciously and creatively engaged in professional activity and possesses such personal qualities as initiative, independence, purposefulness and activity is of particular relevance. The development of these personal qualities in future teachers of Russian should be accompanied by a good command of the language they teach and an orientation toward the culture and traditions of the Russian people. In order to increase the effectiveness of the educational environment of a pedagogical university with a view to preparing students to teach Russian, the authors substantiate a set of pedagogical conditions that contribute to the formation of professional competences necessary for future pedagogical activity.